From Rio Johannesburg and beyond : ways forward for the post-WSSD Commonwealth - Swatuk, Larry A. (2003)
Seeks to determine what the Earth Summit in Rio de Janeiro achieved. Examines some of the initiatives taken by the Commonwealth in the wake of the Johannesburg Summit. Presents a number of challenges for the Commonwealth as an institution for the period beyond Johannesburg.